Optimalisasi Pencatatan Administrasi Pergudangan dengan Kegiatan Stock Opname (Studi Kasus PT XYZ): (Studi Kasus PT XYZ) - Pulungan, Muhammad Dzaky; Tribowo Rachmat (Universitas Sam Ratulangi, 2024)
Warehousing refers to the activities that involve storing products on a large scale in a proper manner and achieving their availability whenever required. In a company, the warehouse has a very important meaning for the flow of goods for the company. A warehouse is a building where goods are stored for commercial purposes and are used by various stakeholders including manufacturers, importers, exporters, wholesalers, and transportation businesses. Warehouses are a key aspect of the modern supply chain and play an important role in the success, or failure, of today's companies. Stocktaking is the activity of counting goods between systems and physical data in the field. Stock taking is an activity of re-collecting data and thoroughly examining company goods to maintain the quality of collections and maximize a company's inventory development activities. In carrying out stock taking, the company can carry out controls, so that it can monitor and know the goods it has. Determining the magnitude of the benefits of stocktaking for the company is very important because stocktaking has a direct effect on the company's income